(untitled) (International Journal of Scientific Pediatrics, 2024)
Summary: This review presents the results of scientific work devoted to the study of biochemical markers of liver damage in respiratory allergies. It has been established that with respiratory allergies in children there is an increase in markers of liver damage without morphological changes. Purpose of the study: to study changes in biochemical markers and morphometric parameters of liver damage in respiratory allergies. Objectives of the study: to examine the concentration of liver enzymes: ALT, AST, alkaline phosphatase, gammaglutamine transpeptidase, as well as IL-4, IL-17A and morphometric parameters of the liver in children with respiratory allergies. Materials and methods. The study was conducted at the Department of Allergology and Gastroenterology of the Bukhara Regional Multidisciplinary Medical Center. 60 children aged 4-10 years were examined and divided into 3 subgroups. The first subgroup included 20 children with bronchial asthma, the second - 20 children with respiratory allergies (allergic rhinitis, sinusitis, allergic tracheitis, bronchitis). The control group 3 consisted of 20 healthy children. All children underwent general and biochemical blood tests (ALT, AST, total bilirubin, alkaline phosphatase (ALP), gamma-glutamyl transpeptidase (GGT), IL-4, IL-17A and liver ultrasound. Results and its discussion. The study of liver transaminases in respiratory allergies made it possible to establish an increase in ALT and AST in patients of group 2 to 44.42±5.9 units/l and 56.1±11.9 units/l, against the control - 25.97±4.15 U/L and 22.69±3.0 U/L, respectively (p<0.005), Table 1. A statistically significant increase in the level of AST in patients of group 2 was established by 2.23 times compared to the indicators for patients in group 1. Consequently, in RA there is an increase in ALT by 1.5 times, AST by 2.23 times than in BA; an increase in the level of alkaline phosphatase by 2.25 times in sick children with BA and by 3.5 times in RA, the latter higher than in children of the control group and with BA, p<0.05; an increase in the level of GGT in patients of group 1 by 5.0 times, in patients of group 2 - by 5.73 times compared to the control - 12.54±3.75 units/l, p<0.05. This indicates involvement of the liver in the pathological process. The results of liver ultrasound show no changes in the structure of the liver. Conclusion. Thus, regardless of the clinical form of manifestation, respiratory allergies occur against the background of systemic inflammation with liver damage in children.